Inward Investment in Northern Ireland and Policy Transfer North and South: 1945 - 1973 - Hearne, Alison (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2022)
Inward Investment in Northern Ireland and Policy Transfer North and South: 1945 -1973 Alison Hearne Using a historical narrative approach (Fletcher and Godley, 2000; Godley 1999), this thesis consists of three interlinked investigations of inward investment into Northern Ireland and the Republic of Ireland between 1945 and 1973. The aim of this thesis is to contribute to an empirical understanding of the nature and extent of inward investment into Northern Ireland, and to explore the relationship between North and South in the context of FDI-related policies. Research paper one focuses on (a) official economic reports and (b) regional agencies/Investment Promotion Agencies (IPAs) involved in the promotion of investment into Northern Ireland after World War Two. Six economic reports carried out between 1952 and 1965 are considered within the context of inward investment. The region was in competition with other UK regions for a share in investment but was simultaneously dependent on central government for financial assistance. The devolved nature of its government, combined with its geographic location set Northern Ireland apart from the rest of the UK. Challenges were also faced by central government as it grappled with the vicissitudes of economic development, inward investment, and regional policy within the wider United Kingdom. Major historical studies on FDI into the United Kingdom (Dunning, 1958; Jones and Bostock, 1996) did not focus specifically on Northern Ireland. Using archival and documentary sources research paper two attempts to readdress this imbalance by providing firm-level information on FDI into Northern Ireland from 1945 to 1973. The third research paper presents an historical exploration of bi-directional policy transfer (Dolowitz and March, 1996, 2000) and Lesson-Drawing (Rose, 1991) between Northern Ireland and the Republic of Ireland regarding FDI policies. The paper concludes that there was significant policy transfer between the two regions, and that policy ideas travelled bi-directionally via numerous modalities of transfer.
APPROVED
Keywords: Northern Ireland; Foreign Direct Investment; Policy Transfer; Economic History; International Business History; Republic of Ireland; Post War Investment; Historical MNE investment